2012
DOI: 10.1152/ajpcell.00198.2011
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the human concentrative nucleoside transporter-1 variant hCNT1S546P provides insight into the sodium-binding pocket

Abstract: SLC28 genes, encoding concentrative nucleoside transporter proteins (CNT), show little genetic variability, although a few single nucleotide polymorphisms (SNPs) have been associated with marked functional disturbances. In particular, human CNT1S546P had been reported to result in negligible thymidine uptake. In this study we have characterized the molecular mechanisms responsible for this apparent loss of function. The hCNT1S546P variant showed an appropriate endoplasmic reticulum export and insertion into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…For example, we showed that the interaction between the C3′ ribose hydroxyl group and Ser 371 on TM7b is important in vcCNT (Figures 1C and 4A). Consistent with our observation, the hCNT1S546P variant is non-functional (Ser 546 in hCNT1 is equivalent to Ser 371 in vcCNT) (Cano-Soldado et al, 2012). Another important finding of our studies is that interactions with the nucleobase and ribose can be additive, and thus the loss of binding energy from modification of part of the nucleoside can be compensated for by the gain of energy from modification of another part of the nucleoside.…”
Section: Discussionsupporting
confidence: 90%
“…For example, we showed that the interaction between the C3′ ribose hydroxyl group and Ser 371 on TM7b is important in vcCNT (Figures 1C and 4A). Consistent with our observation, the hCNT1S546P variant is non-functional (Ser 546 in hCNT1 is equivalent to Ser 371 in vcCNT) (Cano-Soldado et al, 2012). Another important finding of our studies is that interactions with the nucleobase and ribose can be additive, and thus the loss of binding energy from modification of part of the nucleoside can be compensated for by the gain of energy from modification of another part of the nucleoside.…”
Section: Discussionsupporting
confidence: 90%
“…This variant lacks nucleoside transport function, but apparently retains the ability to fold normally and insert into the plasma membrane. 18 Forty-eight hours after infecting cells with an hCNT1S546P adenoviral vector (AdhCNT1SP) at an MOI of 10, no increase in cytidine uptake was observed; in contrast, upregulation of hCNT1-related activity was evident under the same experimental conditions in AdhCNT1-infected cells (Figure 6a). Interestingly, like AdhCNT1, AdhCNT1SP induced cell-cycle arrest at S phase in both NP-9 and NP-29 cells (Figure 6b).…”
Section: Resultsmentioning
confidence: 96%
“…The variant affects a highly conserved residue in the CNT1 protein (Figure ). This specific variant has previously been shown to abolish the nucleoside transporter function of CNT1 . Disruption of this function would result in a biochemical phenotype with unusually high excretion of uridine and cytidine as CNT1 is known to be a high affinity transporter of both pyrimidine nucleosides.…”
Section: Resultsmentioning
confidence: 99%
“…The Ser546 residue of CNT1 is highly conserved in evolution and an analogous serine residue also occurs in the other CNT‐type transporters CNT2 and CNT3 . Based on data from Leabman et al, Gray et al described a high degree of haplotype diversity in SLC28A1 and functionally analyzed coding region variants of the gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation